Antibacterial potential of red dragon fruit peel yogurt (hylocereus spp.) against bacillus subtilis bacteria in hypercholesterolemic wistar rats - Putriningtyas, Natalia Desy; Mardiana, Mardiana; Cahyati, Widya Hary (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2021)
Background: Fruit peel is a part of red dragon fruit that weighed 30-35% of the fruit weight and has not been used optimally. Red dragon fruit peel contains fiber, vitamin, flavonoid, tannin, alkaloids and has the potential as an antibacterial. Red dragon fruit peel can be processed into yogurt.Objectives: This research examined the antibacterial potential of red dragon fruit peel yogurt against Bacillus subtilis in hypercholesterolemic Wistar rats.Materials and Methods: Materials tested in this study were negative control, positive control, and caecum of hypercholesterolemic Wistar. This study used chloramphenicol as the positive control (K+) and DMSO 10% as the negative control (K-). The K1; K2; K3 were orally administered with 1.8 mL; 2.7 mL; 3.6 mL of red dragon fruit peel yogurt, respectively. Red dragon fruit peel yogurt was administered daily for 28 days. Caecum was collected and tested for antibacterial activity using disk diffusion (Kirby Bauer). The Bacillus subtilis was obtained from the Microbiology Laboratory of Center for Food and Nutrition Studies Universitas Gadjah Mada.Results: The average inhibition zone in K-; K+; K1; K2; K3 were 0.00±0.00 mm; 11.5±1.41 mm; 11.5±0.96 mm; 10.13±0.66 mm; 10.38±1.12 mm, respectively. The experimental animal groups, which received 2.7 mL and 1.8 mL of red dragon fruit peel yogurts, showed a significant difference compared to the positive control group (p= 0.026 and p=0.021, respectively). When the dose was increased to 3.6 mL, it showed no statistical difference in results (p=1.000).Conclusions: Red dragon fruit peel yogurt has an antibacterial potential against Bacillus subtilis.